Ovarian follicular dynamics in normal and repeat breeder cows - SHARMA, R K; RAWAL, C V S; HOQUE, M; ANSARI, M R; VARSHEN, V P (The Indian Journal of Animal Reproduction, 2007)
Follicular growth pattern was studied in nonnal and repeat breeder cross bred cows. Ultrasonic studiesrevealed that bovine oestrous cycle is characterized by two or three-wave of follicular growth commonly referredas anovulatory and ovulatory wave. The length of oestrous cycle was significantly higher (P < 0.01) in cowshaving three-wave of follicular growth compar'".d to those having two-wave of follicular growth. The studyrevealed that in two-wave cycle repeat breeder cows have altered pattern of follicular growth compared withnonnal cows. The maximum diameter of anovulatory dominant follicle was significantly higher (P < 0.05) inrepeat breeder cows as compared to those in nonnal cows. Similarly, the ovulatory wave emerged earlier in repeatbreeder cows (P < 0.05). The diameter of corpus luteum on day 8 of cycle was significantly smaller (P < 0:05) inrepeat breeders compared to that in nonnal cows. However, progesterone concentrations did not differsignificantly in nonnal and repeat breeder cows.
Keywords: Cattle; Repeat breeder; Follicular waves; Oestrous cycle